Functionalized Membranes for Photocatalytic Hydrogen Production. Issue 45 (5th October 2014) - Troppmann, Stefan; König, Burkhard
Abstract Functionalized vesicles for photocatalytic hydrogen production in water have been prepared by co‐embedding of amphiphilic photosensitizers and a hydrogen‐evolving catalyst in phospholipid membranes. The self‐assembly allows a simple two‐dimensional arrangement of the multicomponent system with close spatial proximity, which gave turnover numbers up to 165 for the incorporated amphiphilic cobaloxime water reduction catalyst 3 b under optimized conditions in purely aqueous solution. Superior photocatalytic activity in fluid membranes indicates that mobility and dynamic reorganization of catalytic subunits in the membrane promote the visible‐light‐driven hydrogen production. The functionalized membranes represent nanostructured assemblies for hydrogen production in aqueous solution mimicking natural photosynthesis.